2012
DOI: 10.1155/2012/914947
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Deterioration and Associated Pathology Induced by Chronic Low-Level Aluminum Ingestion in a Translational Rat Model Provides an Explanation of Alzheimer's Disease, Tests for Susceptibility and Avenues for Treatment

Abstract: A translational aging rat model for chronic aluminum (Al) neurotoxicity mimics human Al exposure by ingesting Al, throughout middle age and old age, in equivalent amounts to those ingested by Americans from their food, water, and Al additives. Most rats that consumed Al in an amount equivalent to the high end of the human total dietary Al range developed severe cognitive deterioration in old age. High-stage Al accumulation occurred in the entorhinal cortical cells of origin for the perforant pathway and hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 130 publications
3
49
0
1
Order By: Relevance
“…In the present study, the results showed that the spatial learning and memory (SLM) function was significantly impaired in the aluminum-and fluoride-intoxicated group as compared with the control group. This result is in accordance with the previous studies [26][27][28][29][30], whereas the SLM function was significantly reversed in the resveratrol treated against aluminum along with fluoride-treated group as compared to the aluminum along with fluoride-treated group, showing the protective effect of resveratrol. This observation is in agreement with the earlier findings showing protection of resveratrol against neurodegeneration and preserves cognitive function [31][32][33].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the results showed that the spatial learning and memory (SLM) function was significantly impaired in the aluminum-and fluoride-intoxicated group as compared with the control group. This result is in accordance with the previous studies [26][27][28][29][30], whereas the SLM function was significantly reversed in the resveratrol treated against aluminum along with fluoride-treated group as compared to the aluminum along with fluoride-treated group, showing the protective effect of resveratrol. This observation is in agreement with the earlier findings showing protection of resveratrol against neurodegeneration and preserves cognitive function [31][32][33].…”
Section: Discussionsupporting
confidence: 93%
“…It was found that Al could penetrate blood brain barrier, accumulate in brain and the hippocampus had the highest level of Al, which facilitated Al to produce neurotoxic effects (Fattoretti et al, 2004). Among the various adverse effects on CNS, cognitive deficiency has been reported for decades (Rankin, 1993;Shaw and Petrik, 2009;Walton, 2012), while the pre- cise mechanism how this metal exerts damage to memory remains unknown. Therefore, the potential harmful effects of Al on cognitive ability, especially on memory, should be paid more attention in view of its widespread application.…”
Section: Discussionmentioning
confidence: 99%
“…Orally ingestion including by food and water currently comprises the main form of aluminum exposure (97%) for humans (Walton, 2007;Poirier et al, 2011). However, the accumulation of Al is of no physiological or biological function in mammalian species Chen et al, 2010;Walton, 2012) and can even exert neurotoxicity on organisms (Kumar and Gill, 2009;Poirier et al, 2011;Wu et al, 2012). Humans are more vulnerable to Al toxicity (Gonda and Lehotzky, 1996;Flaten, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found that exposure to low levels of Al led to elevation of glial fibrillary astrocytic protein (GFAP) a marker of astrocytic activation (Yokel and O'Callaghan, 1998). Additional persuasive data on the probable harmfulness of Al, comes from observations of cognitive and neuropathological changes characteristic of AD in aged rats after chronic exposure to Al equivalent to that ingested by some human populations (Walton, 2009a,b;Walton and Wang, 2009;Walton, 2012).…”
Section: Experimental Results From Animals Support a Causal Relation mentioning
confidence: 99%